Review of the Secretary's Tasks in Improving Work Effectiveness at the Departement of Labor, Makassar City - Muh. Nasrullah; Sry Adityah Pradana; Muhammad Darwis; Muhammad Jihad Firman; Muh. Rizal S (Universitas Negeri Makassar, 2019)
The process of achieving goals in an organization is needed by the leader in this case a departement head, who is fully responsible for the running of an organization. In carrting out large responcsibilities, a departement head is assisted by a secretary. The Secretary is not only in charge of handling the secretariat but is also the mediator between the leader and his subordinates. Without a secretary, activities involving leaders and correspondence will be neglected. The aim of study is to determine the level of application of secretarial duties in improving work effectiveness at Departemeno of Labor, Makassar City. This research is quantitative descriptive. The population in this study were 119 peoples, while the chosen sample was 32 respondents. The data collection techniques used are observation, questionnaire, interview and documentation. The results of the study showed that the Secretary of the Departemen of Labor, Makassar City in carrying out their duties was in the effective category.